Multi-Modal Data Fusion for Classification of Autism Spectrum Disorder Using Phenotypic and Neuroimaging Data - Kausar, Sumaira; Adnan Younas; Muhammad Yousuf Kamal; Tehsin, Samabia (UMT Artificial Intelligence Review, 2023)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder that causes disrupted social behaviors and interactions of individuals. Hence, it can adversely affect the social functioning of individuals. Each autistic individual is said to have a sort of unique behavioral pattern. ASD has three major sub-categories, namely autism, Asperger, and pervasive developmental disorder, not otherwise specified. The term spectrum indicates that ASD possesses a large variety of symptoms of severity. Practitioners need to have a vast experience and expertise for the accurate analysis of the symptoms of ASD. These symptoms need to be acquired from a range of modalities. An accurate diagnosis requires the analysis of brain scan and phenotypic data. These aspects present a multifold challenge for computer-aided ASD diagnosis. Most of the existing computer aided ASD diagnosis systems are capable of diagnosing only whether an individual is affected with ASD or not. A detailed categorization into the subcategories of ASD in such diagnosis is missing. Another aspect that is missing in the existing techniques is that symptoms are observed from a single modality. This can adversely affect the accuracy of diagnosis, since different modalities focus on different aspects of symptoms. These challenges and gaps provided the motivation to present a method that covers the variety exhibited in ASD, while considering the dire need of acquiring symptoms from a variety of data sources. The proposed method showed rather encouraging results. Moreover, the achieved results are evident of the efficacy of the proposed method.